Efektivitas Interior Rumah Susun 18 m2 dengan Konsep Modular - Ismiranti, Athifa Sri (Waca Cipta Ruang, 2023)
Indonesia is the fourth most populous country in the world, with uneven population distribution, inequality at the economic level, and weak urban planning problems. The issues generated slum areas in big cities that disrupted urban planning, aesthetic image, and public health, then caused environmental and social problems. Vertical development in the form of low-income housing for the middle to lower class effectively addresses the problem of slums and overcrowded areas. However, it needs to be accompanied by a livable design. This research examined a case study of interior design for 18 m2 flats in Bandung City in 2022, with the target population of Bandung City residents, especially those living in slum areas. This research uses a qualitative case study method to provide interior design solutions for flats that are livable, functional, and effective for limited space. The research results showed that movable, foldable and modular furniture designs could produce ergonomic and functional apartment interiors by considering the effectiveness of space. The realization of this design concept has the potential to support Indonesia in having livable, effective, and aesthetic urban planning if supported by the relevant city government